2020
DOI: 10.3390/su12104323
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Pro-Silience Framework: A Literature Review on Quantitative Modelling of Resilient 3PL Supply Chain Network Designs

Abstract: The increasingly dynamic and volatile market environment has elevated the importance of handling operational risks in supply chain networks. Also, black swan risks are constantly evolving and can strike from almost anywhere, including natural disaster, cyber risk, or viruses. As more companies are outsourcing their logistics to third-party logistics (3PL), at the same time, supply chain risks and uncertainties are also shifted to 3PLs. A 3PL’s supply chain network capability to assure continuity can be express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“…With companies focusing more on their core competencies, the outsourcing to LSPs gives shippers exactly the carrier capacity they need and provides flexibility in the supply chain (Wilson, 2020). The on-demand capacity, flexibility and innovations (Grawe, 2009) put LSPs in a strategically crucial position for a company's daily operations and should also help companies to mitigate negative effects arising from an emergency situation such as a supply chain disruption (Gkanatsas and Krikke, 2020;Lam and Dai, 2015;Liu and Lee, 2018). In former crises such as the Icelandic volcano eruption, for example, the LSP DHL were able to reroute flights to Southern Europe and immediately shifted shipments onto trucks and trains to minimize their customers' losses (König and Spinler, 2016).…”
Section: Logistics Service Providers Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…With companies focusing more on their core competencies, the outsourcing to LSPs gives shippers exactly the carrier capacity they need and provides flexibility in the supply chain (Wilson, 2020). The on-demand capacity, flexibility and innovations (Grawe, 2009) put LSPs in a strategically crucial position for a company's daily operations and should also help companies to mitigate negative effects arising from an emergency situation such as a supply chain disruption (Gkanatsas and Krikke, 2020;Lam and Dai, 2015;Liu and Lee, 2018). In former crises such as the Icelandic volcano eruption, for example, the LSP DHL were able to reroute flights to Southern Europe and immediately shifted shipments onto trucks and trains to minimize their customers' losses (König and Spinler, 2016).…”
Section: Logistics Service Providers Resiliencementioning
confidence: 99%
“…As a supply chain can be understood as a network of organizations mutually and co-operatively working to manage the flow of materials and information from suppliers to end users (Lambert, 2008;Christopher, 2011;Lee, 2002), it should be stressed that global supply chains and the associated complex material flows predominately rely on logistics infrastructure (mainly transport and warehouse services) provided by logistics service providers (LSPs). LSPs play and have played a crucial role in the past decades, as companies increasingly focus on their core competencies and have outsourced their logistics functions for transport and warehousing efficiency, flexibility and capacity purposes (Gkanatsas and Krikke, 2020;König and Spinler, 2016;Lam and Dai, 2015;Liu and Lee, 2018;Wilson, 2020). A 2019 LSP study (Infosys, 2019) revealed that 53% of shippers' transportation and 34% of warehousing operations expenditure is related to logistics outsourcing, with supply chain consultancy Gartner (2019) expecting further budget increases for logistics outsourcing in the upcoming years.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, Wang et al (2019) adopted a mean−standard deviation objective function to reflect different risk preferences that a 3PL firm prefers. Gkanatsas and Krikke (2020) contribute toward the development of a resilient 3PL supply chain network. Chu et al (2020) examine whether and when guanxi – an effective relationship management approach in China – is vital for 3PL suppliers as a strategic option to manage environmental reliance.…”
Section: Third-party Logistics (3pl)mentioning
confidence: 99%
“…The virus has exposed weaknesses in global supply chains, originating from the lack of diversification of suppliers, extensive just-in-time strategies which have diminished safety stocks, and inadequate supply chain-wide transparency [24]. Hence, contemporary supply chain scholars highlight the importance of resilience in modern supply chains (e.g., [25,26]). In the latest case studies, suspending production during Covid-19 was an option used as demand declined in a harsh manner, and there were difficulties in the global component supply [2].…”
Section: Literature Review: Epidemics and Effects On The Economy And mentioning
confidence: 99%